Male and female cardiovascular risk in an urban, black working population - Jackson, Lindsay May (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2011)
The aim of this research project was to assess and compare cardiovascular disease (CVD) risk in black males and females from an urban, working population in the Makana (Grahamstown) region of the Eastern Cape, South Africa. Two-hundred and ninety one individuals (males: n = 143, females: n = 148) with a mean age of 42.6 (Â±8.1) years were voluntarily recruited from the greater urban Makana (Grahamstown) area. Eight Cardiovascular disease (CVD) risks were assessed: stature and mass were obtained in order to calculate body mass index (BMI) (mass/stature2). Obesity, defined as a morphological risk, was classified according to the World Health Organisation (WHO) BMI criteria (BMI>30kg.m-2), as well as according to measures of waist circumference (WC) and body composition. Hypertension, hypercholesterolemia and type II diabetes, were grouped as cardiovascular (CV) risks. Hypertension was defined as a blood pressure greater than 140/90mmHg (JNC-7); hypercholesterolemia, as total cholesterol greater than 6.2mmol.L-1 (NCEP); and type II diabetes, as total glucose greater than 12mmol.L-1 (WHO). Physical activity, diet, tobacco use, and alcohol consumption and dependence were grouped as lifestyle-related risks. These were assessed by means of self-reporting through the use of various validated questionnaires. Finally, self-reporting of obesity, hypertension, hypercholesterolemia and type II diabetes was assessed, in addition to perception questions on individuals' perceived body shape and size (Ziebland figures). Self-reported and perceived responses were then compared to actual measures. Females were significantly (p<0.001) heavier than the males (92.7kg compared to 72.1kg) and had significantly (p<0.001) higher BMIs than their male counterparts (37.6kg.m-2 compared to 25.7 kg.-2). They also recorded significantly (p<0.001) higher waist circumference (WC) values and had significantly (p<0.001) higher percentage and total body fat. Significantly (p<0.001) more females were obese (81%) compared to males (17%). While a higher percentage of males (25 % compared to 22%) presented with stage I hypertension (â‰¥140/90mmHg, <160/95mmHg), significantly (p<0.05) more females (14% compared to 8%) presented with stage II hypertension (>160/95mmHg). The prevalence of hypercholesterolemia at a high level of risk (>6.2mmol.L-1) was relatively low (2.1 % of males, 3.4% of females), but notably more participants (22% of males and 26% of females) presented with the condition at a moderate level of risk (>5mmol.L-1). Type II diabetes was the least prevalent CV risk factor, with no males and only 3% of females presenting with the condition. Males consumed significantly (p<0.05) more in terms of total energy intake (9024 vs. 7234 kJ) and were significantly (p<0.05) more active (3315 compared to 2660 MET-mins.week). A significantly (p<0.05) higher percentage of males smoked (51.1% compared to 3.4%), consumed alcohol (73.4% compared to 46.6%) and were alcohol dependent (40% compared to 33.5%). Both males and females tended to be ignorant of their health status, with both samples under-reporting obesity, hypertension and hypercholesterolemia, while over-reporting type II diabetes. Furthermore, obesity was significantly (p<0.05) underestimated, with both male and female individuals perceiving themselves to be notably smaller than they actually were. Physical activity and diet were important determinants of CVD risk in this black urban sample of individuals. Obesity, in particular central adiposity, was the most notable risk (particularly in females), followed by hypertension (particularly in males). Although some risks presented at a moderate level of risk, a clustering of risk factors was evident in both samples, with 12.6% and 41.2% of males and females presenting with two risk factors, and 2.8% and 8.1% of males and females respectively presenting with three risks.
Keywords: Cardiovascular system -- Diseases -- South Africa -- Grahamstown; Obesity -- South Africa -- Grahamstown; Hypertension -- South Africa -- Grahamstown; Hypercholesteremia -- South Africa -- Grahamstown; Diabetes -- South Africa -- Grahamstown; Lifestyles -- Health aspects -- South Africa -- Grahamstown; Health behavior -- South Africa -- Grahamstown; Health attitudes -- South Africa -- Grahamstown; Black people -- South Africa -- Grahamstown -- Health and hygiene